Virtual learning environment: effectiveness in enhancing teaching of vocabulary to secondary ESL learners - Lau, Jacqueline Chung Ling (2019)
The aim of this study was to explore the impact of Frog VLE (Virtual Learning Online) where a class of Form 4 students engaged into the learning of vocabulary and to suggest Frog VLE as a way to improve the students’ performance in vocabulary learning. Besides, English as Second Language (ESL) secondary school learners’ perceptions on the use of Frog VLE in teaching of vocabulary were explored. This study had employed pre-and post-test along with questionnaires and interviews. The study was conducted in SMK Hamid Khan, Tapah, Perak for a duration of eight weeks. The major findings of this research paper showed that majority of the Form 4 students studied improved after receiving the intervention given. The respondents were giving positive feedbacks on the use of Frog VLE in teaching of vocabulary in the class. Future researchers should increase the samples size of the study, preferably to include ESL learners from whole Perak district or even every nation in Malaysia, in order to enable the findings and results of the study to be more generalizable and prove that Frog VLE is truly able to help students in learning vocabulary more effectively.